SharePoint for project managers : how to create a project management information system (PMIS) with SharePoint - Sy, Dux Raymond (O'Reilly Media, 2008)
"Most companies don't understand Microsoft SharePoint's power and use it simply to share documents or spreadsheets. This hands-on book demonstrates how SharePoint can also help you organize and manage complex projects. With SharePoint for Project Management, you'll not only understand how to apply common and practical project management concepts in SharePoint, you'll learn how to build a Project Management Information System (PMIS), customized to your project, that can efficiently coordinate communication and collaboration among team members." "Each chapter includes exercises that let you practice what you learn. Most SharePoint books are either introductory (for end users) or technical (for system administrators), but SharePoint for Project Management is just what project managers need to learn how to harness SharePoint's organizational abilities."--Jacket